Influence of goats feeding on the fatty acids content in milk - Željka Klir; Zvonko Antunović; Josip Novoselec (Mljekarstvo)
Numerous studies have demonstrated the possibility of modeling the content of fatty acids of milk fat, in order to increase the contents of desirable n-3 unsaturated fatty acids and decrease saturated fatty acid with adequate nutrition of goats. Previous studies showed that the milk of goats on pasture increased content of caproic (C6:0), caprylic (C8:0), conjugated linoleic acid (CLA, rumenic acid, cis-9, trans-11 C18:2), linolenic (C18:3), eicosapentaenoic (C20:5) and docosahexaenoic (C22:6) and total content of polyunsaturated fatty acids (PUFA). In the same group of goats lower content of palmitoleic (C16:1), linoleic (C18:2) and total n-6 unsaturated fatty acids was found, as well as lower n-6/n-3 ratio compared with group of goats kept indoors and fed with alfalfa hay. In milk of goats fed with diets supplemented with safflower oil, content of CLA significantly increased, while goats fed with diets supplement with linseed oil had significantly higher content of C18:3 in milk, compared with group of goats fed without addition of these oils. Goats fed with addition of protected fish oil had significant transfer of eicosapentaenoic-EPA and docosahexaenoic-DHA fatty acids in milk. Protected fish oil reduced the negative impact of long chain fatty acids on the activity of ruminal microorganisms, consumption and digestibility of fiber, as well as inhibition of synthesis of fatty acids in milk gland. When adding unprotected fish oil, increase of stearic (C18:0) and oleic (C18:1) fatty acids occurred, because of the biohydrogenation of polyunsaturated fatty acids in rumen.